2017
DOI: 10.2147/sccaa.s138150
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and novel stem cell based therapies for androgenic alopecia

Abstract: The prevalence of androgenic alopecia (AGA) increases with age and it affects both men and women. Patients diagnosed with AGA may experience decreased quality of life, depression, and feel self-conscious. There are a variety of therapeutic options ranging from prescription drugs to non-prescription medications. Currently, AGA involves an annual global market revenue of US$4 billion and a growth rate of 1.8%, indicating a growing consumer market. Although natural and synthetic ingredients can promote hair growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 101 publications
0
36
0
Order By: Relevance
“…e outcomes obtained showed that soluble components had little impact on HF germ generation and Ki67+ cell score inside the organoids although BMP6 and VD3 kept up effectively the DP character in the monolayer culture. Talavera-Adame et al [43] revealed the biomolecular pathway involved in cellular therapy.…”
Section: Discussionmentioning
confidence: 99%
“…e outcomes obtained showed that soluble components had little impact on HF germ generation and Ki67+ cell score inside the organoids although BMP6 and VD3 kept up effectively the DP character in the monolayer culture. Talavera-Adame et al [43] revealed the biomolecular pathway involved in cellular therapy.…”
Section: Discussionmentioning
confidence: 99%
“…is time-consuming, invasive, and costly, all of which limit its acceptance. 3 Other treatment options, including laser therapy, 4 some natural ingredients, 5 and cell culture-derived conditioned medium, 6 are limited by transient results, unpredictable effects, and controversy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hair follicle transplantation is time‐consuming, invasive, and costly, all of which limit its acceptance . Other treatment options, including laser therapy, some natural ingredients, and cell culture‐derived conditioned medium, are limited by transient results, unpredictable effects, and controversy. Novel, effective treatments of androgenic alopecia would be very helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Although hair restoration surgery is nowadays the most effective method, donor hair follicles (HFs) scarcity is often its major limitation . Besides, pharmacological treatments still not fully satisfy the patient's needs and entail drastic side effects . Thus, the limited efficacy and possible side effects of the current treatments have fostered the search for alternative therapeutic solutions, capable of generating unlimited number of HFs de novo.…”
Section: Introductionmentioning
confidence: 99%
“…3 Besides, pharmacological treatments still not fully satisfy the patient's needs and entail drastic side effects. 4 Thus, the limited efficacy and possible side effects of the current treatments have fostered the search for alternative therapeutic solutions, capable of generating unlimited number of HFs de novo. Noteworthy, stem cell-based tissue engineering is emerging as the most thriving approach, aiming to reconstruct HFs in vitro to replace lost or damaged HFs as a consequence of disease, injury, or aging.…”
mentioning
confidence: 99%